Analisis Return On Equity (ROE) Dalam Menilai Tingkat Kesehatan Perusahaan PT. Kalbe Farma Tbk - Ayu Lestari, Vina; Usmar, Andi (Jurnal Ekonomi Bisnis dan Manajemen, 2025)
This study analyzes the financial condition of PT Kalbe Farma Tbk from 2023 to 2025 using Return on Equity (ROE) as the primary assessment indicator. ROE is an essential profitability ratio that evaluates the company’s ability to generate net income based on shareholders’ equity. Quarterly ROE data were collected and averaged annually to detect patterns of change and assess the company’s financial status. The findings indicate that ROE in 2023 was very low, reflecting weak profitability and limitations in managing equity effectively. In 2024, ROE increased despite considerable fluctuations, indicating that the company was entering a recovery phase. In 2025, ROE rose steadily and exceeded the healthy threshold, demonstrating improved operational efficiency and stronger financial performance. Overall, the study concludes that PT Kalbe Farma Tbk experienced a gradual recovery and achieved a healthy financial condition by the end of the analysis period.